Comparative Study of Financial Performance Among Co-operatives in Nepal: With Reference to Awasar, Dhanakunja, and Nilganga in KTM Metropolitan-16 - Dhakal, Chuda Prasad (Journal of Development Review, 2024)
This study compares the financial performance of three cooperatives in Kathmandu Metropolitan-16: Awasar Saving and Credit Cooperatives Ltd., Dhanakunja Saving and Credit Cooperatives Ltd., and Nilganga Saving and Credit Cooperatives Ltd. The objectives are to analyze their financial health using key financial ratios over five years (2069-070 to 2073-074 BS). First-hand data were collected to compute two liquidity ratios (current ratio and debt-equity ratio), three profitability ratios (return on investment, return on assets, and return on equity), and one market prospect ratio (earnings per share). The results indicate that all three cooperatives struggle to achieve significant profitability, with most profitability ratios remaining below 1%. Awasar showed the highest return on equity at 6% in its second year. Dhanakunja displayed the strongest liquidity position, while Awasar and Nilganga consistently had current ratios below the satisfactory level of 2:1. Despite low debt-to-equity ratios suggesting stable businesses, market prospects varied, with Awasar performing relatively better than Nilganga. This comparative analysis provides a model for assessing the financial health of cooperatives and can guide future studies.